Ovum pick-up technique in recently weaned ewe lambs subjected to ovarian stimulation - Teixeira, Pedro Paulo Maia [UNESP] (2015)
Background: The purpose of this study was to evaluate the effectiveness and possible complications of the laparoscopic ovum pick-up (LOPU) technique and to optimize ovarian stimulation in recently weaned ewe lambs.Materials, Methods &Results: Thirty-six healthy lambs, aging 4-8 weeks, were used in this study and divided into six different groups of six animals. Intravaginal implants of medroxyprogesterone were used for follicular wave induction, and parenteral equine chorionic gonadotropin (eCG) and follicle stimulating hormone (FSH) were administered for ovarian stimulation. Ewes from group GCN did not receive any treatment. In group GCI, the animals received only intravaginal implants. For other groups, ovarian stimulation was carried out as follows: in Group G80U, ewes were treated with a single dose of 80 mg of FSHp; in Group G80M, ewes received 4 administrations of 20 mg FSH, in Group G160U, they were treated with a single dose of 160 mg FSH; and in Group G160M they received 4 administrations of 40 mg FSH). Quantitative and qualitative assessment of retrieved oocytes were carried out after LOPU. In vitro maturation (IVM) of oocytes was also quantitative and qualitatively analyzed. Surgical procedure was divided into 6 stages and overall and stage surgical times were assessed. Post-operative pain and plasma fibrinogen were also assessed. The mean overall surgical time was 24.3 +/- 5.2 min. Post-operative pain scores and plasma fibrinogen did not differ significantly from baseline values (P > 0.05). The number of oocytes recovered from GCN, GCI, G80U, G80M, G160U and G160M were 1.1 +/- 1.6, 1.1 +/- 1.8, 4.6 +/- 3.2, 2.2 +/- 0, 8, 5.8 +/- 3.1 and 3.0 +/- 2.0, respectively, and the rates of viable oocytes retrieved were 57.0%, 14.2%, 51.7%, 18.0%, 70.2% and 33.3%, respectively.Discussion: In spite of the risk of anesthesia, the incidence of regurgitation and rumen distention was low, which were reported as mild complications. The risk of reduced lung volume, hypoxia, increased intrathoracic and vascular pressure and increased cardiac stress were managed using assisted ventilation and short duration of the surgical procedure. No iatrogenic damage to the viscera occurred. The blind insertion of the first trocar without previous pneumoperitoneum as performed in the current study was safe and optimized surgery. Adhesion formation was not observed in the current study. The formation of adhesion could have been prevented by careful manipulation of the reproductive tract and removal of clots from the ovarian surface with 0.9% NaCl solution. The excellent recovery of the animals and the absence of mild/severe pain were attributed to the minimally invasive nature of the laparoscopic procedure. The average number of visualized and aspirated follicles, retrieved oocytes and the oocyte recovery rates for G80U and G160U were similar to those reported by studies in adult sheep. An extremely low IVM rate has been reported in sheep. In the current study, the use of 160 mg of FSH in a single dose (G160U) obtained similar cytoplasmic and nuclear maturation results to those observed in adult sheep. It is thus suggested that weaned ewe lambs may require high concentrations of exogenous FSH to produce a higher number of better quality follicles and to achieve superior in vitro maturation rates. Thus, the groups treated with a single-douse of 80 mg of FSH or on a fractional administration regimen possibly did not achieve sufficient serum levels for adequate follicular growth. The best results including IVM were observed for the G160U group, which showed promising commercial viability.